1996
DOI: 10.1074/jbc.271.24.14169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Essential Signaling Cascade for Mitogen-activated Protein Kinase Activation by Angiotensin II in Cultured Rat Vascular Smooth Muscle Cells

Abstract: In cultured rat vascular smooth muscle cells, angiotensin II (Ang II) induced a rapid increase in mitogen-activated protein kinase (MAPK) activity through the Ang II type 1 receptor, which was insensitive to pertussis toxin but was abolished by the phospholipase C inhibitor, U73122. The Ang II-induced MAPK activation was not affected by the protein kinase C inhibitor, GF109203X, and was only partially impaired by pretreatment with a phorbol ester, whereas both treatments completely prevented MAPK activation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
192
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(216 citation statements)
references
References 74 publications
22
192
2
Order By: Relevance
“…Although the answer to this question is not yet known, a modest amount of speculation may be appropriate here. Certain receptors coupled to pertussis-toxin-sensitive G proteins can trigger activation of Srcrelated tyrosine kinases, Ras and ERK through a stimulatory pathway that contains PI-PLC and CaM (27,28). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the answer to this question is not yet known, a modest amount of speculation may be appropriate here. Certain receptors coupled to pertussis-toxin-sensitive G proteins can trigger activation of Srcrelated tyrosine kinases, Ras and ERK through a stimulatory pathway that contains PI-PLC and CaM (27,28). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CaM antagonists can either block (27,28) or prolong (46) the activation of ERKs in various cell types. Because ERKs are effector proteins for the small GTPase Ras, we examined the effects of CaM antagonists on the activation of Ras, MEK, and ERK in neutrophils (Figs.…”
Section: Effects Of Ca 2ϩ /Cam Antagonists On the Activation Of Ras Amentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, p21ras has been documented to be involved in Gq and phospholipase (PL) C mediated Ang II signaling in cardiac myocytes (7) and vascular smooth muscle cells (8). However, the sequential upstream events linking this GPCR to p21ras were not delineated but seemed to involve the Shc-Grb2-Sos adapter proteins in cardiac myocytes (7).…”
mentioning
confidence: 99%
“…It has been suggested that this Ca 2+ -dependent tyrosine kinase could be related to another Ca 2+ -dependent tyrosine kinase, PYK2, previously described in neuronal cells. 98 Another class of tyrosine kinases linked to AT 1 receptor activation is the Janus kinase (JAK) family. The JAK/STAT pathway is a signalling pathway comprising a number of tyrosine kinases and transcription factors.…”
Section: Phospholipase C (Plc)mentioning
confidence: 99%